Exceptional talent in the 21st century context: Conceptual framework, definition, assessment, and development. (May 2021) - Maker, C June
With problem-solving as the focus and wisdom as the goal, the concept of giftedness is reconceptualized in the 21st century context. The two most prominent constructs in the field of education for the gifted, creativity and intelligence, are integrated into a view of exceptional talent as consisting of the ability and willingness to solve complex problems, the ability to solve varied types of problems, and a highly integrated and interconnected knowledge base. Both intelligence and creativity involve similar processes, but these processes are used in different ways during the problem-solving process. Using the framework of a paradigm as outlined by Dai and Chen, the elements of a different perspective resulting from more than 40 years of developing a conceptual framework, implementing practices based on that framework, and research on these practices are presented: definition (What?), assessment (Who?), purpose (Why?), and development (How?).